Catalytic Properties of the 3-Chlorocatechol-Oxidizing 2,3-Dihydroxybiphenyl 1,2-Dioxygenase from Sphingomonas sp. Strain BN6 - Riegert, Ulrich (American Society for Microbiology, 1999)
The 2,3-dihydroxybiphenyl dioxygenase from Sphingomonas sp. strain BN6 (BphC1-BN6) differs from most other extradiol dioxygenases by its ability to oxidize 3-chlorocatechol to 3-chloro-2-hydroxymuconic semialdehyde by a distal cleavage mechanism. The turnover of different substrates and the effects of various inhibitors on BphC1-BN6 were compared with those of another 2,3-dihydroxybiphenyl dioxygenase from the same strain (BphC2-BN6) as well as with those of the archetypical catechol 2,3-dioxygenase (C23O-mt2) encoded by the TOL plasmid. Cell extracts containing C23O-mt2 or BphC2-BN6 converted the relevant substrates with an almost constant rate for at least 10 min, whereas BphC1-BN6 was inactivated significantly within the first minutes during the turnover of all substrates tested. Furthermore, BphC1-BN6 was much more sensitive than the other two enzymes to inactivation by the Fe(II) ion-chelating compound o-phenanthroline. The reason for inactivation of BphC1-BN6 appeared to be the loss of the weakly bound ferrous ion, which is the cofactor in the catalytic center. A mutant enzyme of BphC1-BN6 constructed by site-directed mutagenesis showed a higher stability to inactivation by o-phenanthroline and an increased catalytic efficiency for the conversion of 2,3-dihydroxybiphenyl and 3-methylcatechol but was still inactivated during substrate oxidation.